2015
DOI: 10.1021/acs.est.5b01428
|View full text |Cite
|
Sign up to set email alerts
|

Silver Dissolution and Release from Ceramic Water Filters

Abstract: Application of silver nanoparticles (nAg) or silver nitrate (AgNO3) has been shown to improve the microbiological efficacy of ceramic water filters used for household water treatment. Silver release, however, can lead to undesirable health effects and reduced filter effectiveness over time. The objectives of this study were to evaluate the contribution of nanoparticle detachment, dissolution, and cation exchange to silver elution, and to estimate silver retention under different influent water chemistries. Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 29 publications
5
49
1
1
Order By: Relevance
“…12,13 Thus, there is an increased interest in using biodegradable and biocompatible reducing agents to prepare AgNPs. Over the last decade, polysaccharide-based biopolymers such as alginate, starch, and chitosan [14][15][16] have been used as green alternatives [17][18][19][20] to conventional agents due to their low-cost, nontoxicity, and environment-friendly properties. In most cases, the chemical dispersants used for controlling the growth of metallic nanoparticles were replaced by these biopolymers due to their low-toxicity to animal cells.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Thus, there is an increased interest in using biodegradable and biocompatible reducing agents to prepare AgNPs. Over the last decade, polysaccharide-based biopolymers such as alginate, starch, and chitosan [14][15][16] have been used as green alternatives [17][18][19][20] to conventional agents due to their low-cost, nontoxicity, and environment-friendly properties. In most cases, the chemical dispersants used for controlling the growth of metallic nanoparticles were replaced by these biopolymers due to their low-toxicity to animal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Dans un premier temps, l'objectif était de définir les volumes d'eau (solvant) à utiliser afin de pouvoir effectuer l'extrusion de la pâte de façon efficace. les différentes granulométries de coques de riz ont été définis en se basant sur les travaux de différents auteurs dans la littérature (Bielefeldt et al, 2010;Kallman et al, 2011;Ren and Smith 2013;Mittelman et al, 2015).…”
Section: Composition Des Pâtes Céramiquesunclassified
“…AgNPs can have considerable activity against bacteria, fungi, and even some viruses [1][2][3][4][5][6] making them attractive to companies interested in manufacturing products with food safety or sanitary bene ts. A variety of consumer products now contain AgNPs, including food contact materials [7][8][9], clothing and personal care products [10,11] dietary supplements [12], and water lters [13,14]. Additionally, many studies have shown that simulated use of AgNPs-containing consumer products can result in AgNPs release from these products into the environment [7,8,10,11,15].…”
Section: Introductionmentioning
confidence: 99%